SASTRA REMAJA (TEENLIT) SEBAGAI MEDIA ALTERNATIF DALAM MENINGKATKAN BUDAYA LITERASI - Ninawati Syahrul (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. The presence of adolescent literature - known as teenlit- is a necessity so loved by the teenagers. As one of the literary genres, teenlit seems to be not too complicated. In addition to the story plot that is easy to trace, the style of language is "lively" and the content is centered around teenage world. Teenlit spreading on social media online always gets variety of responses. In short, teenlit is a phenomenon in the adolescent literature. Issues discussed in this study can be formulated as whether teenlit can be used as a medium to improve the literacy culture among adolescents? This research aims to examine and explore how far teenlit can be used as a medium to improve the literacy culture among adolescents. To that end, to teach and appreciate the teenlit literature, teacher should use methods that are varied and close to adolescent life: discussion, questioning, simulation, or the like. Such contextual approaches are the key element in popularizing teenlit for the learner's life. The results of the study indicate that teenlit can be used as an alternative media in increasing the literacy of learners. Literacy not only means to be able to read, but also able to understand the contents of the reading. Thus, the moral message—seventeen commendable characters, including tolerance and unity in diversity, as promoted by by the Government, will be reflected in the actions and behavior of adolescents in the future. Keywords: teenlit, learning, literacy culture, adolescent